2021
DOI: 10.1116/6.0001109
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals epitaxy and remote epitaxy of LiNbO3 thin films by pulsed laser deposition

Abstract: Nonlinear oxides such as LiNbO3 have found many applications in both conventional electro-optics and quantum optics. In this work, we demonstrate the van der Waals and remote epitaxy of LiNbO3 films on muscovite mica and graphene-buffered sapphire, respectively, by pulsed laser deposition. Structural analysis shows that the epitaxial relation in van der Waals epitaxy is LiNbO3 (0001) || mica (001) and LiNbO3 [011¯0] || mica [010] with LiNbO3 [101¯0] || mica [010], a 60°-rotated twin structure. The relation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…4b). 348 Besides, 2D materials that have a minuscule thickness limit their interaction length with electromagnetic waves, 50 and recent advances on remote epitaxy [371][372][373] and van der Waals epitaxy [374][375][376] also permit various three-dimensional (3D) freestanding nanomembranes (Fig. 4c), 50,375,[377][378][379][380] as well as other 3D layer exfoliation techniques by epitaxial chemical lift-off, mechanical exfoliation or laser lift-off.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…4b). 348 Besides, 2D materials that have a minuscule thickness limit their interaction length with electromagnetic waves, 50 and recent advances on remote epitaxy [371][372][373] and van der Waals epitaxy [374][375][376] also permit various three-dimensional (3D) freestanding nanomembranes (Fig. 4c), 50,375,[377][378][379][380] as well as other 3D layer exfoliation techniques by epitaxial chemical lift-off, mechanical exfoliation or laser lift-off.…”
Section: Perspectivesmentioning
confidence: 99%
“…348 Besides, 2D materials that have a minuscule thickness limit their interaction length with electromagnetic waves, 50 and recent advances on remote epitaxy [371][372][373] and van der Waals epitaxy [374][375][376] also permit various three-dimensional (3D) freestanding nanomembranes (Fig. 4c), 50,375,[377][378][379][380] as well as other 3D layer exfoliation techniques by epitaxial chemical lift-off, mechanical exfoliation or laser lift-off. 68,[381][382][383][384][385][386] These thin films are also made ultrathin with artificially defined van der Waals interfaces for photonic van der Waals integration, 48,50,120 on graphene-covered templates for defect-reduced heteroepitaxy (Fig.…”
Section: Perspectivesmentioning
confidence: 99%
“…Remote epitaxy has been demonstrated in the growth of various ionic compounds such as III–V, II–VI, and I–VII, complex oxides, halide perovskites, etc. ,, Among them, commercial manufacturing typically uses metal–organic chemical vapor deposition (MOCVD) at high temperature (over 1000 °C) under a hydrogen atmosphere for the growth of III–nitrides, such as GaN, AlN, and AlGaN. However, a recent study by Park et al revealed that the harsh conditions required for MOCVD growth of GaN can instigate thermochemical decomposition of both graphene and underlying nitrides, thereby limiting the full exploitation of remote epitaxy for III–nitrides-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, epitaxial films rarely exhibit bulklike properties. van der Waals (vdW) epitaxy [44][45][46][47][48][49][50] provides a route to mitigate these problems. In vdW epitaxy, the epilayer has the single-crystal-like crystalline coherence of standard epitaxial films, yet the interface is only weakly bonded by vdW interactions.…”
Section: Introductionmentioning
confidence: 99%